He was not alone: Bosman in context - Borja Garcia-Garcia (2016)
This chapter analyses the social, political, historical and economic context of the Bosman case. The chapter argues that Bosman needs to be understood as yet another stage of a continued process of commercialisation and transformation in European football. Football players fought to transform their employment conditions since the 1960s. Clubs questioned the legitimacy of UEFA to regulate European football and organise club competitions as they wanted a larger share of the commercial profits of the game. Finally, political institutions in Brussels started to exert pressure on football governing bodies to modify the international transfer system. The chapter argues that, taking these into account, major transformations in the governance and regulation structures of football were needed, and they would have happened even without the Bosman ruling. Consequently, Bosman cannot be seen, on its own, as the only cause of the transformation of modern football in Europe. Finally, the chapter dedicates some space to Jean Marc Bosman’s legal team composed by Luc Misson and Jean Louis Dupont. It was their legal expertise what made a challenge before the Belgian and European courts also possible.